The link between non-routine problem solving success levels and strategic flexibility of gifted fourth-grade students - Keleş, Taliha; Yazgan, Yeliz (Frontiers in Psychology, 2025)
IntroductionThe purpose of this correlational study is to explore how success levels in solving non-routine problems among gifted fourth-grade students are linked to their strategic flexibility.MethodsData were gathered from 165 gifted fourth-grade students at a Science and Art Center in Bursa/Türkiye. Binary logistic regression was employed to assess the impact of gender and various indicators of strategic flexibility on success levels in non-routine problem solving.ResultsThe findings reveal that these students perform exceptionally well in both non-routine problem solving and strategic flexibility. The most commonly used strategies among students are “drawing figures or diagrams”, “reasoning”, and “working backward.” The strategic flexibility indicators with the highest average usage are “selection of the appropriate strategy”, “strategy knowledge”, and “changing strategies when encountering different problems”. A significant and strong correlation was observed between their success in non-routine problem solving and strategic flexibility. Within the regression model, the ability to “select appropriate strategies” emerged as a significant predictor of performance in non-routine problem solving among gifted students.DiscussionIn summary, this study highlights the problem solving strategies used by gifted students in non-routine problems, and the indicators of strategic flexibility that are effective in predicting success.